A Tepid Liberation: Sectarianism in Scholarship on Hōnen and Women - Gillson, Gwendolyn (Journal of Religion in Japan, 2025)
Hōnen (1133-1212) is celebrated as the founder of Pure Land Buddhism in Japan, particularly by the Jōdoshū (Pure Land Sect). Scholar-priests continue to publish on what they see as Hōnen’s revolutionary agenda and promulgation of the correct form of Pure Land Buddhism. Their examination of Hōnen’s doctrines is wide ranging but an area that has received little attention is Hōnen’s understanding of women. This article will analyze some of the only articles on this topic published by Jōdoshū sectarian scholars to argue that even though the authors attempt to champion Hōnen’s advocacy for "gender equality," their concern is less in promoting or even helping women but instead advocating for Jōdoshū as the true inheritor of Pure Land Buddhist doctrine. Their articles demonstrate part of a broader narrative amongst scholars of Japanese Buddhism that prioritizes the goals of sectarian institutions even when producing secular scholarship.